Attribute-Based Proxy Re-encryption for Health Record Maintenance in Cloud Environment - et. al., Sathis Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In cloud secure individual information sharing is the significant issues since it makes a few protections and information privacy issue while getting to the cloud administrations. Numerous difficulties present in close to home information sharing, for example, information security assurance, adaptable information sharing, proficient position designation, calculation effectiveness enhancement, are staying toward accomplishing functional fine-grained admittance control in the Personal Health Information Sharing framework. Individual wellbeing records should be encoded to ensure security prior to moving to the cloud. Targeting addressing the above difficulties, here propose a productive information sharing instrument for Personal Data Sharing, which not just accomplishes information security, fine-grained admittance control and authority assignment all the while, yet in addition advances the calculation effectiveness and is appropriate for asset compelled workers. A large portion of the information purchasers are straightforward, while not many of them are bad and will spillage their mystery keys in the intrigue. Despite what might be expected, PKG and information proprietor are thought to be completely confidential. Moreover, public cloud 1 and public cloud 2 can't conspire with one another. The non-tricky supposition that is sensible, on the grounds that the customer can request that two cloud workers can't uncover client’s data by contract. In proposed work, PR-ABE (Attribute Based Encryption with Proxy Re-encryption) method executes to give secure encryption of clinical information. To improve the concurrency control, here halfway key sharing plan will be executed. Utilizing this, information proprietor can send halfway mystery key for the mentioned client. This methodology conquers the key speculating assault in information recovery measure.